Evaluasi Kualitas Aplikasi Digital Korlantas Polri guna Mendukung Tugas Kepolisian dalam Rangka Penguatan Pelayanan Publik: Aplikasi digital korlantas Polri - Raslin, Harvin; Astuti, Septi; Yusuf, Annisa; Suryadi, Suryadi; Taryana, Yana (Pusat Penelitian dan Pengembangan Polri, 2024)
The transformation toward Polri Presisi is a priority program led by Police Chief General Drs. Listyo Sigit Prabowo, M.Si., aimed at modernizing public service facilities to facilitate public access to Polri services. One implementation of this initiative is the launch of digital services by the Traffic Corps (Korlantas), including the SIM Nasional Presisi (SINAR) for driver’s licenses, the National Digital Samsat (SIGNAL) for vehicle tax payments, Electronic Traffic Law Enforcement (ETLE), and the Integrated Road Safety Management System (IRSMS) for traffic accident monitoring. This research aims to evaluate the Korlantas digital applications (SINAR, SIGNAL, ETLE, and IRSMS) to ensure they meet Polri's ICT Master Plan standards as mandated by Police Chief Decree No. 704/V/2018, providing fast, easy, and transparent service while protecting users' personal data. The study utilizes a qualitative and quantitative approach, collecting data through interviews, observations, and questionnaires. Findings indicate that Korlantas digital applications have progressed but require improvement in areas such as hosting on private data centers, optimal integration, data processing efficiency, and security management. The applications are viewed as beneficial by the public, though many are not fully aware of features like SINAR, SIGNAL, and ETLE, necessitating broader outreach. This evaluation offers valuable insights for enhancing Korlantas applications to better support police services for the community.